Using neural networks to improve business process efficiency - Jumageldinov, I.M.; Omarova, A.T.; Takuova, Z.S. (Академик Е.А.Бөкетов атындағы Қарағанды университетінің баспасы, 2024)
In modern business, neural networks have become a key tool for enhancing efficiency and competitiveness. Their ability to analyze large volumes of data, identify hidden patterns, and automate complex processes opens up new opportunities for optimizing various aspects of company operations. Neural networks are used for demand forecasting, supply chain management, customer experience personalization, risk prevention, and cost reduction. With the advancement of technology, their applications will continue to expand, encompassing new industries and business tasks. This paper examines the key benefits and prospects of using neural networks, as well as their contribution to the digital transformation of business.
Keywords: neural networks; artificial intelligence (ai); business processes; data analysis; pattern recognition; big data processing; predictive analytics; recommendation systems; quality control; predictive maintenance; logistics; supply chain management; marketing; personalization; fraud detection; cybersecurity; cost reduction; strategic planning; self-learning systems; healthcare; energy; environmental protection